Review of Fund Work on Trade. (Policy Papers; Policy Paper, 2005)
The Fund has responded to a number of recent challenges facing its members by stepping up its work on trade. The Fund's trade agenda has been shaped by both Executive Board guidance and demands on missions. The present report assesses the Fund's priorities in the trade area, takes stock of its work, and reviews the Fund's collaboration and division of labor with other institutions.